A Preliminary Study on the Germination of Uraria picta (Jacq.) DC. - Pokle, H.B. Waghire*, S.A. Survase; D.S. (Journal of Ecobiotechnology, 2011)
The germination response of Uraria picta to different treatments viz. water soaking for 24 h and 72 h, hot water 50 ± 2 oC and 80 ± 2 oC, conc. HCl, conc. H2SO4, BAP, IAA, IBA and Kinetin was investigated. The higher percentage of germination ( 80% ) occur in conc. H2SO4 for 10 min and lower percentage of germination ( 10 % ) occur in 50 ± 2 0 C, 80± 20 C and conc. H2SO4 for 5 min i.e.10 % .There was no any response on germination by the treatment of hormones and conc. HCl, water soaking for 24 and 72 h.